Producing long melon in off-season - Singh, Awani Kumar; Sabir, Naved; Shridhar, Shridhar; Singh, Veerpal; Singh, Ajeet; Kumar, Anil (Indian Horticulture, 2019)
Long melon is generally cultivated traditionally in specific local area of riverbed cum Dieara-Land areas and its fruits are available only during summer season (February-May) and not during other seasons or off-season (August-February) under open field condition due to erratic climatic and weather conditions. This off-season gap of Kakari production can be fulfilled vide its cultivation under protected structures facilitated by hand pollination or bees pollination because of cross-pollinated nature of the crop. In addition, this crop would be highly successful for diversification of protected structures. Therefore, production of long melon during off-season has a lot of scope for higher income. The crop can be grown successfully under insect proof-net-house and naturally-ventilated polyhouse structures for supply of high quality long melon to the up-market available in Delhi and other big cities of the country during September-February which will be highly profitable as it is used in all religious functions for prasad, salad and also cooking. Also, greenhouse cultivation of ‘kakari’ is technologically feasible and economically profitable for farmers due to lesser problems of pests such as nematodes, thrips and mites.